Rheolytic Pharmacomechanical Thrombectomy in Renal Dialysis Arteriovenous Fistula and Graft Thrombosis: Outcomes from a Tertiary Hospital in Qatar - Ahmad L. F. Yasin; Sohaib Zoghoul; Ahmad N. Al-Ekeer; Yaman M. Alahmad; Ali Barah; Saad Rehman; Omran Almokdad; Qayed Al-Debyani; Ayman Elmagdoub; Rahil Hussein Kassamali (The Arab Journal of Interventional Radiology)
Purpose To investigate the ability to salvage an acutely thrombosed dialysis access using rheolytic pharmacomechanical thrombectomy (PMT), the short- and medium-term patency rates and safety at a tertiary care hospital.